The effectiveness and safety of acupuncture for patients with myopia: A protocol for a systematic review and meta-analysis. Issue 23 (5th June 2020) - Yu, Zengfang; Wang, Xinxin; Zhao, Xiaoshuang; Li, Dan; Duan, Junguo
Abstract: Background: Myopia is a common visual disorder which has become a public health problem worldwide. Myopia and high myopia are substantial risk factors for severe visual impairment and other serious eye diseases. Acupuncture used to prevent and control myopia is a common practice in China, but it is controversial in other countries. This study aims to evaluate the efficacy and safety of acupuncture in delaying the progression of myopia in children and adolescents through systematic evaluation. Methods and analysis: The following electronic databases will be searched from inception to November 2019 regardless of publication status and language: Medline, EMBASE, Web of Science, the Cochrane Library, PubMed, China National Knowledge Infrastructure (CNKI), China Biology Medicine (CBM), Chinese Scientific Journal Database (VIP), Wanfang Database, Chinese Biomedical Literature Database (CBLD), Chinese Science and Technology Periodical Database (CSTPD). RCT registration websites, including http://www.ClinicalTrials.gov and http://www.chictr.org.cn, will also be searched. Review Manager V.5.3 will be used to analysis the statistic. Two reviewers (ZY and XW) will independently select studies, extract and code the data, assess risk of bias of the included studies, evaluate the quality of evidence for outcomes. Results: This study will provide a rational synthesis of current evidences for acupuncture to delay the progression for myopia in children and adolescents. Conclusion: The conclusion of this study will provide evidence for evaluating the efficacy and safety of acupuncture to delay the progression for myopia in children and adolescents. Abstract : Supplemental Digital Content is available in the text